2009
DOI: 10.1021/ma9017058
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Poly(butylene terephthalate) from the Glass

Abstract: Crystallization from the glass of poly(butylene terephthalate) (PBT) has been investigated by small-angle X-ray scattering and differential scanning calorimetry. When PBT crystallizes from the glassy state, the nodule crystalline structures in nanometer scale forms and the micrometer order objects, i.e., spherulites, are not observed. The nodule size grows and saturates at a given annealing temperature and increases with increasing annealing temperature. Two temperatures are obtained by the linear extrapolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…5 reveals small crystal grains, suggesting that they are not spherulites as the crystals lack the typical spheroid radiating crystal pattern. The crystallization of PBF is thus similar to PBT, which mainly gives a-crystalline without observing spherulites when crystallized from the molten state [46].…”
Section: Resultsmentioning
confidence: 77%
“…5 reveals small crystal grains, suggesting that they are not spherulites as the crystals lack the typical spheroid radiating crystal pattern. The crystallization of PBF is thus similar to PBT, which mainly gives a-crystalline without observing spherulites when crystallized from the molten state [46].…”
Section: Resultsmentioning
confidence: 77%
“…In the temperature range of 30e160 C, only the detectable glass transition of annealed fibers remains. One small but distinct melting peak is observed for all polyester fibers slightly above 200 C, which is attributed to the annealing effect [5,6,21]. In addition, a major melting peak is detected at a higher temperature.…”
Section: Electrospun-fiber Induced Transcrystallization Of Ippmentioning
confidence: 81%
“…For all as-spun fibers, a small but distinct endotherm at 57e58 C is observed, and a huge endotherm associated with crystal melting behavior is initially detected at 190 C and ends at~230 C, with an apparent peak located at 222 C. The absence of any exothermic peak between two endotherms further supports that the as-spun PBT fibers are not in the amorphous state. Upon heating, the imperfect phase can undergo a structural transformation to become more stable and perfect aform prior to its melting [6]. To reveal the plausible crystal perfection and structural transformation, the stepwise heating of the PBT fibers was performed, and the corresponding WAXD profiles at different temperature (T a ) are shown in Fig.…”
Section: Entanglement Concentration (F E ) and Concentration Effect Omentioning
confidence: 99%
See 1 more Smart Citation
“…Because the ( À104) plane is almost perpendicular to the c axis, the ( À104) interplanar spacing reveals the conformational change from all-trans to gauche-trans-gauche during the crystal-crystal transition. Song 17 proposed that a mesophase structure forms when amorphous PBT is stretched at room temperature, and Konishi and Miyamoto 18 suggested that a mesophase structure on the nanometer scale forms when PBT crystallizes from the glassy state. This mesophase, which has a quasi-smectic fibrillar structure as revealed by the (001 0 ) reflection, transformed into the a-form.…”
Section: Neck Drawing and Time Resolutionmentioning
confidence: 99%